Workers with special needs and their professional integration - BENTOUATI, Maroua (Social Sciences Journal, 2019)
The attention of any community of people with special needs is the norm through which we can judge the progress of this society. Work is an important means of satisfying many of the needs and motives of the individual and, if it is generally applicable to the general public, is particularly true for the disabled, as it may prompt them to compensate for what they may feel in the professional sphere. Through this study, we will highlight the concept of people with special needs and address disability, its characteristics and types, as well as the employment as a right, and we will deal with professional integration as part of social integration through the integration of the disabled in his profession, this enables him to exercise life Natural, and from investing its residual capabilities